Imagining Siberia: Cartographic Motive in the Novel of A. Ivanov Tobol - Julia Snežko (Literatūra (Vilnius))
The The article considers the role of cartographic motif in the conceptualisation of space in Russian writer Alexei Ivanov’s novel Tobol. The paper reveals the connection of this motif with the main plot lines of the novel, with the structure of the novelistic space, as well as with its ideological component. The study concludes that the map functions both as a tool for traversing space (and thus conquering it), as a means of awakening poetic imagination, and as a crucial element in attempts to imagine Siberia. Drawing on the ideas of American geographer Yi-Fu Tuan, the article shows that the map in the novel is one of the most important elements in the attempt to transform space into place.